Black seed oil-alginate nanoemulsion characteristics utilising an ultrasonicator at pilot plant scale - Mohd Rus, Shaiqah; Mohd Rus, Anika Zafiah; Mohmad Sabere, Awis Sukarni; Abu Bakar, Mohd Rushdi; Mohamed, Farahidah; Doolaane, Abd Monem (ResearchersLinks Ltd, 2024)
Black seed oil (BSO) contains thymoquinone, an active ingredient that is well-known for its antioxidant property and used in food and traditional medicine. BSO is encapsulated in micrometre-sized alginate beads (AB), to increase its palatability. This encapsulation is established and produced on a small scale in the lab. To achieve the ideal BSO alginate nanoemulsion during large-scale manufacturing, it is vital to use suitable parameters where two parameters were manipulated: the flow rate of the pump and the percentage of the power (amplitude) of the ultrasonicator. The droplet size, PdI, and zeta potential of the nanoemulsion were investigated. The zeta potential values for BSO nanoemulsions ranging from -53.83 ± 1.50 to −63.50 ± 0.66 mV. All zeta values were below -30 mV, demonstrating that the nanoemulsions are stable emulsions. Each amplitude and flow rate produced BSO alginate nanoemulsion within the targeted droplet size, which is below 500 nm of the sonication process, except at flow rates 144, 216 and 288 mL min-1 at 30 % power of amplitude. The droplet size was found to be smaller at a lower flow rate. The smallest droplet size was achieved at 72 mL min-1 i.e., 346.57 nm to the power of 90% of ultrasonicator amplitude. For every flow rate of 70% and 90% power of sonication, the PdI of BSO alginate nanoemulsion was less than 0.700, The PdI ranges for these parameters are from 0.262 ± 0.005 to 0.627 ± 0.045. The higher the flow rate and the low percentage of ultrasonicator power, the larger the particle size of the BSO alginate nanoemulsion obtained. As the applied power of the amplitude increases from the optimal value (70%), the size of the emulsion particle decreases. It is discovered that the BSO alginate nanoemulsion particle size is influenced by the pump flow rate and ultrasonicator power.